Diversity-oriented approach to natural product inspired pyrano-carbazole derivatives: strategic utilization of hetero-Diels–Alder reaction, Fischer indolization and the Suzuki–Miyaura cross-coupling reaction. Issue 47 (25th November 2015) - Kotha, Sambasivarao; Ali, Rashid; Saifuddin, Mohammad
Abstract: A variety of natural products inspired pyrano-carbazole derivatives have been assembled via hetero-Diels–Alder reaction and Fischer indolization (FI) under operationally simple reaction conditions. Later, the scope of this methodology has been expanded through Suzuki–Miyaura cross-coupling reaction involving different boronic acids. This simple strategy can be useful to generate a variety of medicinally important carbazole derivatives. Graphical abstract: